Simulation-based assessment of urban heat island mitigation in commercial districts - Miftahul Huda; Respati Wikantiyoso; Nurul Aini; Pindo Tutuko; Erlina Laksmiani Wahjutami (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
Commercial districts in tropical cities are especially vulnerable to the Urban Heat Island (UHI) effect, leading to higher outdoor air temperatures and poorer microclimate conditions. This study examines the efficiency of UHI mitigation strategies to lower the outdoor air temperature in a commercial area in Malang, Indonesia. The research utilized ENVI-met microclimate simulation software to analyse the effectiveness of different UHI mitigation strategies. Four mitigation strategies were developed: structural-based, vegetation-based, material-based, and an integrated mitigation approach. The results were compared to the current conditions. Simulations were conducted to represent the hottest day during the dry season, measuring air temperature at a height of 1.4 m throughout the day. The results indicate that all mitigation scenarios maintain a similar daily temperature pattern to the current condition, with peak air temperatures occurring in the early afternoon. The major difference among all mitigation strategies is the amount of cooling effect. The structural-based mitigation scenario provides the minimum amount of cooling effect, at 0.12 °C. The vegetation-based mitigation scenario provides 0.38 °C, while the material-based mitigation scenario provides 0.61 °C. The integrated mitigation scenarioproduced the greatest cooling effect, reducing the temperature by 0.86 °C. These findings demonstrate that integrated, multi-mechanism strategies can effectively reduce daytime heat exposure in tropical commercial areas, while also showing the need for additional comfort assessments that look beyond just air temperature.